SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TELADAN MENGGUNAKAN METODE COMPOSITE PERFORMANCE INDEX (CPI) PADA SMK NEGERI 1 KOTABUMI - Rustam Rustam; Pakarti Riswanto; Dwi Marisa Efendi; Asep Afandi; Supriyanto .; Sidik Rahmatullah; Sigit Mintoro; Desri Arisandi (STMIK Dian Cipta Cendikia Kotabumi, 2022)
SMK Negeri 1 Kotabumi is one of the Vocational High Schools that conduct the selection of exemplary teachers in the hope that the selection of exemplary teachers can spur teachers to further improve the quality in teaching. The assessment of exemplary teachers also still uses manual methods carried out using assessment sheets carried out by the committee, so it takes a longer time and the results obtained have not been maximal. In this study, the use of the Composite Performance Index (CPI) Method can be implemented into the PHP programming language and produce decisions that are in accordance with the criteria for selecting exemplary teachers, based on sample data used as many as 10 teacher data, Widodo, Spd.MM with a score of 2191.67 was decided to be an exemplary teacher.